Features of Structural Inhomogeneities in Doped Cadmium Antimonide Crystals - Koval, Yu. V.; Zakharchuk, D. A.; Yashchynskyy, L. V.; Panasyuk, L. I.; Fedosov, S. A. (Physics and Chemistry of Solid State, 2017)
The paper presents the results of research to identify inhomogeneities in tellurium doped CdSb crystals. The work aims to investigate the influence of structural inhomogeneities and establish the presence of periodicity in the distribution of data inhomogeneities. It was found with a two-probe compensation method, optical topography method, scanning electron microscopy, and EDX-analysis the presence layered structure with several layers of types, characterized by different periods.